Analysis of the Implementation of Occupational Safety and Health Management (OSH) at the Search and Rescue Office, Class B, Nias: - Telaumbanua, Sri Lestari; Telaumbanua, Aferiaman; Gea, Jeliswan Berkat Iman Jaya; Batee, Maria Magdalena (ProBisnis : Jurnal Manajemen, 2024)
Occupational Safety and Health (K3) is a protection for workers and other people who enter the workplace against the dangers of work accidents with the aim of preventing, reducing the risk of work-related diseases and accidents as well as improving the health status of workers so that their work productivity increases. The aim of this research is to determine the implementation of Occupational Safety and Health (K3) management at the Class B Nias Search and Rescue Office. In conducting research, the research method used is a descriptive research method with a qualitative approach. Based on the research results, The implementation of K3 Management at the Class B Nias Search and Rescue Office has been implemented and carried out well based on existing SOPs, carrying out training, education, use of PPE, as well as supervision and audits so that maximum results can be achieved. However, there are still workers who do not comply with the use of PPE when carrying out their duties. So what agencies do is carry out training, education, use of PPE, as well as supervision and audits so that they can achieve maximum results. The Nias Class B Search and Rescue Office carries out K3 implementation such as providing PPE, providing first aid boxes to anticipate work accidents or work illnesses and the agency also always urges workers to always remember work safety by wearing PPE correctly before carrying out work in the field.